Words of Turkic origin in ancient Greek - Hajar Huseynova (Turkic Studies Journal, 2021)
The article notes the functioning of turkisms in many languages of the world, including Greek, English, French, Russian and other languages. It is known that the Turks established socio-political and cultural ties with many ancient peoples, and sometimes settled on the territories of these peoples or in areas close to them. Such areal contacts caused language and lexical borrowings. N.A. Baskakov in the book “Russian surnames of Turkish origin”, wrote that the origins of 300 noble Russian families go back to Turkic roots, including genealogy and the scientist A.Kh. Khalikov notes numerous Turkic words in the Russian language. In the book “500 generations of Turkish-Bulgarian-Tatar origin, known as Russian”, he explores 500 surnames of Turkic origin. In the book “Turks in the ancestral roots of the Russians” also gives information about the origin of the Turks and the Turkic generations, known as the Russian generation. According to Chingiz Aitmatov, one third of Russian words are Turkic. Similar language Turkish loanwords are observed in ancient Greek and modern Greek, which is the subject of this article. According to some researchers, the Indo-European languages on the territory of the Balkan Peninsula appeared thanks to the Greeks. Even in ancient times, researchers noted that in the territory of modern Greece once lived people who did not speak the Indo-European language, which is approximately 2500 BC. The era of 2500-1600 BC is associated with the Hittites, later the Greeks settled on the territory of Hellas. According to some researchers, the most ancient inhabitants of the territory of Ancient Greece were the traki, whose language was later assimilated with the language of the hittites, and then the Greeks. In ancient scandinavian sources, there are relics of the language of tracts belonging to the Western branch of the proturks, which is confirmed by the praturkian vocabulary and onomastics. The Greek-Turkic language substrata and units imprinted in ancient Greek confirm the presence of Turkic loanwords, which have not lost their relevance in modern language contacts between Turkish and Greek.